Osip tekmovalno najuspešnejših mladih v slovenski atletiki - Železnik, Lea (Šport (Ljubljana), 2018)
In the article issues, related to dropout of young sportsmen in competitive athletics, are discussed. Sample was created on the basis of IAAF scoring tables from 1993 till 2004. We took 10 best young athletes from every chosen discipline. We were curious if there exist differences between complexes of those disciplines (sprints, jumps, throws, middle- and long-distance runs) and what percentage of young athletes (U16) manage to achieve visible results in absolute age category on national and international level. We also studied dynamics of individual`s development of sports career. The main finding of the research is that dropout in Slovenian competitive athletics is very big. We proved some more facts: (1) decrease is not influenced by the complex of disciplines; (2) competitively the most successful young athletes (first 5 on the scoring tables) insist in chosen sport longer, more often take place on greater international championships and more frequently hold national records in comparison with those youths, who are not on the top in age category U16; (3) furthermore very young (13 and 14 years old) and at the same time very successful athletes also more frequently reach the absolute age category and are achieving better results on national as well as on international level.
Keywords: atletika; mladi; osip; razvoj; tekmovalni šport; uspešnost